2017
DOI: 10.1503/cmaj.161156
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and maternal morbidity and mortality after attempted operative vaginal delivery at midpelvic station

Abstract: When there is an arrest in the descent of the fetal head at midpelvic station during the second stage of labour, mode of delivery and perinatal and maternal outcomes are largely dependent on the urgency to expedite delivery and operator skill with midpelvic operative vaginal delivery.1,2 Operative vaginal delivery provides a temporal advantage over cesarean delivery, although midpelvic forceps or vacuum application requires skill and experience. Although cesarean delivery generally decreases the risk of birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 26 publications
3
53
2
Order By: Relevance
“…However, an ecological design is appropriate for assessing associations at the population level, 22,23 and individual-level studies also show that operative vaginal deliveries cause obstetric and birth trauma. [6][7][8][9] Measurement of pelvic Note: ARR = adjusted rate ratio, CI = confidence interval, OVD = operative vaginal delivery. *ARRs and 95% CIs expressing the change in obstetric trauma and severe birth trauma rates per 1% absolute increase in OVD rates and associated number of excess cases per year, term singleton deliveries, Canada, 2004-2014; includes data from Alberta, Manitoba, Ontario, and Saskatchewan.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an ecological design is appropriate for assessing associations at the population level, 22,23 and individual-level studies also show that operative vaginal deliveries cause obstetric and birth trauma. [6][7][8][9] Measurement of pelvic Note: ARR = adjusted rate ratio, CI = confidence interval, OVD = operative vaginal delivery. *ARRs and 95% CIs expressing the change in obstetric trauma and severe birth trauma rates per 1% absolute increase in OVD rates and associated number of excess cases per year, term singleton deliveries, Canada, 2004-2014; includes data from Alberta, Manitoba, Ontario, and Saskatchewan.…”
Section: Limitationsmentioning
confidence: 99%
“…5 Such recommendations for addressing increases in cesarean delivery are premised on the assumption that operative vaginal delivery has greater relative safety compared with cesarean delivery. However, recent studies [6][7][8][9] have shown higher rates of severe perinatal and maternal adverse outcomes after operative vaginal delivery. In particular, our previous work 6,7 showed substantially higher rates of obstetric trauma among midpelvic forceps and vacuum deliveries, compared with cesarean deliveries (adjusted rate ratio [ARR] 8.48, 95% confidence interval [CI] 7.22-9.96 and 6.90, 95% CI 5.86-8.13, respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equally importantly, pregnant women have little understanding of the issues relating to expertise in midcavity operative vaginal delivery, and our study findings reflect the experience and skills of contemporary practitioners. Also, in a previous study based on pan-Canadian data, 4 we showed that the effect of operative vaginal delivery on perinatal and maternal severe morbidity/mortality was not modified by institutional delivery volume. Finally, if the caesarean delivery group benefited from more skilled operators and less complicated fetal positions (as postulated by Mohan et al 1 ), then the effect of midcavity operative vaginal delivery on perinatal and maternal severe morbidity/mortality documented in our study represent underestimates of the true effect.…”
Section: Referencesmentioning
confidence: 47%
“…Lastly, given the results of our studies comparing perinatal and maternal morbidity and mortality following OVD versus caesarean delivery, we would be cautious in interpreting a decreased rate of caesarean delivery per se as evidence of more discriminating assessments in the absence of a formal assessment of corresponding outcome rates.…”
mentioning
confidence: 99%